Helplessness of Words. Ante Kesić’s “Fiction” on the Holocaust - Czerwiński, Maciej (Poznańskie Studia Slawistyczne, 2017)
In the article one book written by the Croatian author, Ante Kesić, is taken into consideration. The novel Black Snow, published in 1957, narrates about a Slovenian young woman, Breda, who was caught by the Germans in Ljubljana (for her contacts with communist partisans) and sent to the Dachau Concentration Camp. Although not of Jewish origins she encounters the Holocaust of the Jews in the camp and gets pregnant with a Jewish artist. The novel conceptualizes tragedy of war and the Holocaust in a very experimental way, by using a range of modernist, avant-garde or even surrealist literary techniques. The author attempts to invent a new language with a new grammar that would enable to express something that is not expressible.